PBSA/layered silicate nanocomposites and the role of nanoclay on their electrospun fibrous structure. (23rd August 2010) - Tsimpliaraki, Athanasia; Svinterikos, Stratis; Panayiotou, Costas; Marras, Sotirios I.; Zuburtikudis, Ioannis; Papadopoulou, Lambrini
Polymer nanocomposites based on poly (butylene succinate-co-butylene adipate) (PBSA) with various concentrations of organically modified montmorillonite were fabricated by the solvent casting technique. The morphology of the prepared materials was investigated by X-ray diffraction (XRD) and their thermal behaviour was analysed by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Fibrous mats of pure and nanocomposite PBSA were subsequently prepared by electrospinning. Solution concentration, flow rate and applied voltage were kept constant in order to reveal the effect of the clay content alone on the final fibrous structure using scanning electron microscopy (SEM).